EFFECT OF DOSAGE OF REDISPUTABLE POWDERS AND THE TYPE OF LOW-MODULAR INCLUSIONS ON THE PROPERTIES OF FINE-AGGREGATE CONCRETE - A. V. Dolgova; G. V. Nesvetaev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Reliability and durability of structures using materials with various properties (plaster coatings, cement glue, new concrete during repair and restoration of structures, etc.) largely depends on the adhesion of the layers and the deformation properties of the coatings. To obtain the required properties of materials used for coatings, modifiers based on polymers and low-modulus inclusions are introduced into the composition of new concretes, for example, entrained air. The aim of the work is to identify some patterns of change in the properties of concrete with the joint introduction of these modifiers.Method Experimental determination of the tensile strength in bending, compression, E-modulus, adhesion to the concrete base by standard methods.Result The influence of separate and joint introduction of dispersible polymer powders and various low-modulus inclusions into the composition of fine-grained concrete has been established.Conclusion The joint introduction to the composition of fine-grained concrete of various low-modulus inclusions and redispersible polymer powders provides a reduction in the stress level during forced deformations due to the different effects additives on the strength and deformation properties and contributes to increased adhesion to the concrete.